Propuesta etnoeducativa: la formación del mundo desde dos perspectivas diferentes - Callejas Arévalo, Ronal Enrique; Rueda Velasco, Yeni Milena; Salazar Garzón, Franceidy Andrea (Revista Científica, 2011)
The Colombian Constitution is clear in stating that education is a service and a right that should be given to every people independent of his ethnic origin, recognizing the multiethnic and multicultural character of our country. Thus this work is aimed to recognize the world view that members of the “Cabildo Muisca” at Bosa, Colombia, have about the Word’s origin and compare it with the one proposed by the physicists. To recognize that knowledge, we propose a didactical strategy that respectfully and cordially shows both, the muisca’s worldview and the physicists’ representation of the word’s origin. In this didactical strategy an interactive story is presented to muiscas’s children, whose ages are from 7 to 9. This strategy consists of three major phases which are reflected in the story, entitled, How much do we know? Let us recognize two types of knowledge and Let us reflect. In each of these phases there is a group of activities for the reader to interact with the story aimed to generate an active attitude while the strategy is being carried out.